Multiwavelength high-order optical vortex detection and demultiplexing coding using a metasurface - Yang, Dahai; Lin, Jie; Chen, Chen; Li, Chang; Hao, Junbo; Lv, Baiying; Zhou, Keya; Wang, Yiqun; Jin, Peng (Advanced Photonics Nexus, 2022)
. Orbital angular momentum (OAM) of an optical vortex has attracted great interest from the scientific community due to its significant values in high-capacity optical communications such as mode or wavelength division multiplexer/demultiplexer. Although several configurations have been developed to demultiplex an optical vortex, the multiwavelength high-order optical vortex (HOOV) demultiplexer remains elusive due to lack of effective control technologies. In this study, we present the design, fabrication, and test of metasurface optical elements for multiwavelength HOOV demultiplexing based on optical gyrator transformation transformations in the visible light range. Its realization in a metasurface form enables the combined measurement of OAM, the radial index p, and wavelength using a single optical component. Each wavelength channel HOOV can be independently converted to a high-order Hermitian–Gaussian beam mode, and each of the OAM beams is demultiplexed at the converter output. Furthermore, we extend the scheme to realize encoding of the three-digit gray code by controlling the wavelength or polarization state. Experimental results obtained at three wavelengths in the visible band exhibit good agreement with the numerical modeling. With the merits of ultracompact device size, simple optical configuration, and HOOV recognition ability, our approach may provide great potential applications in photonic integrated devices and systems for high-capacity and demultiplex-channel OAM communication.